Identifikasi Learning Loss Pasca Pandemi Covid-19 pada Mata Pelajaran Matematika Siswa Kelas XI di MAN 1 Sintang - Maharani Gunawan, Desty Anisa; Hamdani, Hamdani; Bistari, Bistari (AS-SABIQUN, 2024)
The purpose of this study was to find out and describe the topic and factors that cause class XI Mia 1 MAN 1 Sintang students to experience learning loss after the Covid-19 pandemic in mathematics subjects. The research method used in this research is descriptive qualitative research with the subjects of this research being class XI Mia 1 MAN 1 Sintang students, totaling 34 people. Data collection techniques use written tests, questionnaires and interviews. The results of the written test research showed that students experienced learning loss in mathematics as much as 2.95% in the low category and 91.17% in the very low category. Based on questionnaire and interview analysis, it shows that the main factors that students experience learning loss are due to unstable signals, decreased learning motivation, and limited interaction between teachers and students and between students and students.